Effect of individual factors on knowledge sharing - Eugene, Okyere-Kwakye; Md Nor, Khalil; Ziaei, Seyyedali; Huan, Hon Tat (2010)
Knowledge management has been acknowledged as an important element for businesses today. While individuals within the organisations might recognize the importance of knowledge management for the success of their day to day business functions, previous literatures have shown that individuals are still reluctant to participate in knowledge management efforts especially knowledge sharing. As the behaviour people show in different situations depends highly on their personal character traits as well as the social forces, the degree of the reluctance or willingness towards sharing their knowledge might also fit in the same case.This paper suggests a relationship between knowledge sharing and four of the individual factors namely altruism, self efficacy, mutual reciprocity and trust.